2021
DOI: 10.3390/su13073856
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment with Integrated Circular Economy Principles: A Toy Case Study

Abstract: When considering the sustainability of production processes, research studies usually emphasise environmental impacts and do not adequately address economic and social impacts. Toy production is no exception when it comes to assessing sustainability. Previous research on toys has focused solely on assessing environmental aspects and neglected social and economic aspects. This paper presents a sustainability assessment of a toy using environmental life cycle assessment, life cycle costing, and social life cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Since such questions are the focus of this research, the advantage of this case study approach is obvious. In addition, this case study methodology is often applied to analyze life cycles and ES [6,7,76] due to specific context factors, such as a unique situation, a long-term time frame, and high complexity. Similar context factors are also expected in the analysis of ES decision making in BCs.…”
Section: Case Study Methods and Multiple Case Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Since such questions are the focus of this research, the advantage of this case study approach is obvious. In addition, this case study methodology is often applied to analyze life cycles and ES [6,7,76] due to specific context factors, such as a unique situation, a long-term time frame, and high complexity. Similar context factors are also expected in the analysis of ES decision making in BCs.…”
Section: Case Study Methods and Multiple Case Designmentioning
confidence: 99%
“…As such, it would be a sustainable choice to buy a product with a higher price today if lower operating costs can be achieved in the future. Life cycles are widely considered in the discourse about sustainability in general, or for specific applications, such as toys or even circular economies [5][6][7]. Generally, it is no surprise that cost information and cost structures are seen as appropriate indicators for ES (e.g., reference [8]).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also suggested integrating studies on consumer purchasing behavior with strategies aimed at reducing environmental impact, increasing toy durability, and maintaining profitability in the toy industry. However, past research presented in Table 1 had underscored the significance of taking into account the use phase of a toy's life cycle, which is often uncontrollable and unpredictable (Lukman et al, 2021; Muñoz et al, 2009). Lukman et al (2021) performed a thorough sustainability evaluation of a toy, taking into account environmental, economic, and social aspects but neglecting the use and end‐of‐life phases.…”
Section: Introductionmentioning
confidence: 99%
“…Soca is the only database available for the performance of an integrated LCSA. So far, it has only been used in a few articles (Erauskin‐Tolosa et al., 2021, Kovačič et al., 2021, Penadés‐Plà et al., 2020) and EU project reports (Brown et al., 2019). As indicated by Brown et al.…”
Section: Introductionmentioning
confidence: 99%